Association between Maternal Mental Health and Child Stunting in Indonesia - Tyas, Annisa Purbaning; Setyonaluri, Diahhadi (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
This study aims to study maternal mental health’s association to stunting in children under five years old in Indonesia, which is related to mothers, children, and households’ characteristics based on the age group of children under five years old. This study uses longitudinal data from the Indonesian Family Life Survey (IFLS) in 2007 and 2014 with the Logistic Regression method. Maternal mental health was measured using the CESD-10 instrument. The results showed that in the children’s age group of 0-59 months and 24-59 months, an increase in the total CESD-10 score was associated with stunting in children after being controlled by all the characteristics. At age 0-23 months, the increase in the total score of CESD-10 was not associated with stunting. Maternal height, breastfeeding duration, child age, birth weight, and residence location were associated with stunting in all age groups. Maternal education and expenditure quintiles were associated with stunting in the 0-59 months and 24-59 months age groups. Meanwhile, two variables only relate to the incidence of stunting in one age group of children under five, namely maternal age (0-59 months of children under five) and sanitary conditions (24-59 months of children under five).